2022
DOI: 10.1186/s43088-022-00314-z
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive assessment and risk factors of liver fibrosis in pediatric patients with beta thalassemia major using transient elastography

Abstract: Background In beta-thalassemia major (TM) patients, levels of liver iron overload and the presence of chronic hepatitis C are directly correlated with the onset and severity of liver fibrosis. A noninvasive approach that can evaluate cirrhosis and liver fibrosis in these patients is transient elastography (TE). We aimed to find out the role of noninvasive elastography in the assessment of liver fibrosis in young beta-thalassemia major patients receiving frequent blood transfusions. Identifying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
0
0
Order By: Relevance
“…The median value of SGPT was 38 IU/L, with a minimum value of 9 IU/L and a maximum value of 314 IU/L, which is higher than the values reported by Ferraioli et al [16] at 27 IU/L. The mean creatinine levels for our study were found to be 0.8 mg/dl, which is comparable to the results of previous research [11].…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The median value of SGPT was 38 IU/L, with a minimum value of 9 IU/L and a maximum value of 314 IU/L, which is higher than the values reported by Ferraioli et al [16] at 27 IU/L. The mean creatinine levels for our study were found to be 0.8 mg/dl, which is comparable to the results of previous research [11].…”
Section: Discussionsupporting
confidence: 69%
“…Consistent with previous research, our findings demonstrated a statistically significant positive correlation (r= 0.287; p= 0.033) between serum ferritin levels and hepatic fibrosis. In a study by Mohamed et al [ 11 ], serum ferritin levels were substantially correlated with hepatic fibrosis in thalassemia major patients. Several other studies [ 12 - 17 ] have also reported a significant positive correlation between serum ferritin levels and hepatic fibrosis.…”
Section: Discussionmentioning
confidence: 99%